Membaca Pikiran Gus Dur dan Amin Rais Tentang Demokrasi - MASDAR, Umaruddin 1972- (Pustaka Pelajar, 1999)
Democracy from a Sunnites' perspective; comparative study of the political thoughts of Abdurrahman Wahid and Amien Rais, two Indonesian Muslim political leaders and intellectuals.